Application of Upscaling Permeability Workflow: Pore to Core Plug Scale on Malay Basin Thin Sections - Luluan Almanna Lubis, ZZ Tuan Harith, KA Moh Noh, H Khairy, A Mo, . (2012)
The main purpose of this paper is to present the application of our newly permeability prediction workflow which can be implemented in real time on standard personal computer.